2016
DOI: 10.5301/hipint.5000408
|View full text |Cite|
|
Sign up to set email alerts
|

Mini-Open Approach for Femoroacetabular Impingement: 10 Years Experience and Evolved Indications

Abstract: According to our experience there are several presentations of FAI and associated hip conditions, where other authors advocate surgical dislocation, which can be conducted through a mini-open approach when increased surgical skills are reached. Moreover, this technique was found to be useful as an additional tool to consider, even for surgeons involved in the arthroscopic learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
9
0
3
Order By: Relevance
“…The risk factors of failure in the treatment of FAI were investigated in many studies [14, 18, 19, 21, 29]. Our results were comparable to those reported in other literature, showing that younger patients and patients in the early stages of hip osteoarthritis (Tönnis 0 or Tönnis I) might benefit from surgical treatments [9, 19]. Boone et al supposed that caution should be taken to perform surgical dislocation in patients over the age of 40 [30]; in our series using minimally invasive approach, patients younger than 55 still gained benefit from the surgery.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The risk factors of failure in the treatment of FAI were investigated in many studies [14, 18, 19, 21, 29]. Our results were comparable to those reported in other literature, showing that younger patients and patients in the early stages of hip osteoarthritis (Tönnis 0 or Tönnis I) might benefit from surgical treatments [9, 19]. Boone et al supposed that caution should be taken to perform surgical dislocation in patients over the age of 40 [30]; in our series using minimally invasive approach, patients younger than 55 still gained benefit from the surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported the results of using mini-open technique in the treatment of FAI [8, 9, 19]. Most of the authors used anterior Hueter approach on an extension table or fracture table, taking the advantage of intermuscular and internervous dissection [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported good results in the management of patients with FAI using an anterior Hueter approach. 5 , 20 , 29 , 30 However, the anterior Hueter approach might make it difficult to access the subspine space. Cohen et al 7 managed FAI in athletes using a direct mini-open approach and demonstrated significant improvement in functional outcomes.…”
Section: Discussionmentioning
confidence: 99%